Strengthening Existing Laboratory-Based Systems vs. Investing in Point-of-Care Assays for Early Infant Diagnosis of HIV: A Model-Based Cost-Effectiveness Analysis. (1st July 2020) - McCann, Nicole C.; Cohn, Jennifer; Flanagan, Clare; Sacks, Emma; Mukherjee, Sushant; Walensky, Rochelle P.; Adetunji, Oluwarantimi; Maeka, Kenneth K.; Panella, Christopher; Chadambuka, Addmore; Mafaune, Haurovi; Odhiambo, Collins; et al.
Abstract : Background: To improve early infant HIV diagnosis (EID) programs, options include replacing laboratory-based tests with point-of-care (POC) assays or investing in strengthened systems for sample transport and result return. Setting: We used the CEPAC-Pediatric model to examine clinical benefits and costs of 3 EID strategies in Zimbabwe for infants 6 weeks of age. Methods: We examined (1) laboratory-based EID ( LAB), (2) strengthened laboratory-based EID ( S-LAB), and (3) POC EID (POC). LAB/S-LAB and POC assays differed in sensitivity ( LAB / S-LAB 100%, POC 96.9%) and specificity ( LAB / S-LAB 99.6%, POC 99.9%). LAB/S-LAB/POC algorithms also differed in: probability of result return (79%/91%/98%), time until result return (61/53/1 days), probability of initiating antiretroviral therapy (ART) after positive result (52%/71%/86%), and total cost/test ($18.10/$30.47/$30.71). We projected life expectancy (LE) and average lifetime per-person cost for all HIV-exposed infants. We calculated incremental cost-effectiveness ratios (ICERs) from discounted (3%/year) LE and costs in $/year-of-life saved (YLS), defining cost effective as an ICER <$580/YLS (reflecting programs providing 2 vs. 1 ART regimens). In sensitivity analyses, we varied differences between S-LAB and POC in result return probability, result return time, ART initiation probability, and cost. Results: For infants who acquired HIV, LAB/S-LAB/POC led to projected one-year survival of 67.3%/69.9%/75.6% and undiscounted LE of 21.74/22.71/24.49 years. For all HIV-exposed infants, undiscounted LE was 63.35/63.38/63.43 years, at discounted lifetime costs of $200/220/240 per infant . In cost-effectiveness analysis, S-LAB was an inefficient use of resources; the ICER of POC vs. LAB was $830/YLS. Conclusions: Current EID programs will attain greater benefit from investing in POC EID rather than strengthening laboratory-based systems. Abstract : Supplemental Digital Content is Available in the Text.